PEMBAKUAN AKTIVITAS PERGUDANGAN DENGAN STANDARD OPERATING PROCEDURE (SOP) DI PT. XYZ - Sitorus, Erwin; Nasution, Siti Soraya Faiza (TALENTA Publisher, 2017)
In realizing professional, effective, and efficient work, as well as improvement of work system, the company requires Standard Operating Procedures (SOP). SOP is a guide or reference to perform job tasks in accordance with the function and also a tool of performance appraisal company based on technical, administrative, and procedural indicators in accordance with work procedures and work system in the work unit concerned. Problems that occurred at PT. XYZ is the absence of standardization and documentation of work standards for warehousing activities resulting in non-standard work quality. The purpose of this research is to arrange Standard Operating Procedure (SOP) based on work elements in each warehousing activities in warehouse of PT. XYZ. The result of the research is the preparation of SOP for the acceptance of coffee beans, the storage of coffee beans, the delivery of coffee beans to the production, and the delivery of coffee to the consumers.